2020
DOI: 10.1002/agj2.20211
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of plant density and nitrogen regimes to mitigate lodging risk in wheat

Abstract: Influences of planting density and nitrogen rate have been investigated frequently in targeted wheat (Triticum aestivum L.) research. Few studies have investigated interactions between these inputs. The objective was to determine the combine effect of N and seeding rates on culm morph‐physiological traits for lodging tolerance and grain yield. The experiment used a split‐split randomized block design using two wheat varieties ‘AnNong0711’ and ‘YanNong19’, split by four seeding (180, 240, 300, and 375 × 104 ha−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
(71 reference statements)
2
8
0
Order By: Relevance
“…Additionally, global wheat yields are predicted to significantly increase with rising CO 2 , though these gains are highly dependent on growing temperatures, water availability, and nitrogen fertilization 5 , 12 , 59 . Furthermore, typical high planting densities in wheat may increase plant height and lodging risk due to increased intra and inter-plant competition 60 . Increased nitrogen fertilization to maintain grain protein and improve yield at elevated CO 2 was found to be only somewhat effective; however, increased nitrogen fertilizer rates did increase internode length, plant height, and ultimately lodging risk 61 , 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, global wheat yields are predicted to significantly increase with rising CO 2 , though these gains are highly dependent on growing temperatures, water availability, and nitrogen fertilization 5 , 12 , 59 . Furthermore, typical high planting densities in wheat may increase plant height and lodging risk due to increased intra and inter-plant competition 60 . Increased nitrogen fertilization to maintain grain protein and improve yield at elevated CO 2 was found to be only somewhat effective; however, increased nitrogen fertilizer rates did increase internode length, plant height, and ultimately lodging risk 61 , 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Plant lodging was null in PG rainfed , despite greater plant height, spike density per area, grain yield, N accumulated in the SDM, and water availability (as compared to L rainfed ), all factors that predispose plants to lodging (Ma et al, 2016;Khan et al, 2020). Another factor that increases lodging is the wind speed (Ma et al, 2016).…”
Section: Weather and Field Conditions Influences On Wheat Cropmentioning
confidence: 99%
“…Therefore, we hypothesize that the plant lodging tolerance in PG rainfed might have been associated with the greater culm resistance favored by the environmental conditions. In this context, Zhang et al (2017) evaluated the culm structure and concluded that wheat plants that have culm with a thicker cell wall and denser basal internodes are less susceptible to lodging and that these features can be improved with the proper use of N. In addition, the optimization of N fertilization management can also reduce plant lodging-including for susceptible cultivars-by favoring the accumulation of lignin and cellulose, which can decrease the rate of culm breaking (Chen et al, 2018;Khan et al, 2020).…”
Section: Weather and Field Conditions Influences On Wheat Cropmentioning
confidence: 99%
“…It is worth noting that secondary cell walls also provide mechanical strength for structural support. Stem strength was significantly positively correlated with stem secondary wall thickness in crops such as rice ( Oryza sativa ; Zhang, Yao, et al., 2022) and wheat ( Triticum aestivum ; Khan et al., 2020), and in ornamental plants such as herbaceous peony ( Paeonia lactiflora Pall. ; Zhao, Shi, et al., 2020).…”
Section: Introductionmentioning
confidence: 99%